Large‐Area, Nanometer‐Scale Discrete Doping of Semiconductors via Block Copolymer Self‐Assembly. Issue 18 (22nd September 2015) - Popere, Bhooshan C.; Russ, Boris; Heitsch, Andrew T.; Trefonas, Peter; Segalman, Rachel A.
Abstract : A novel platform for "nanoconfined" doping of planar semiconductors is based on block copolymer self‐assembly. This methodology enables precise control over incorporated dopant positions in all three spatial dimensions on the nanoscopic length scale, along with the local dopant concentration, demonstrating a significant advancement in the ability to confine dopant atoms at the technologically relevant length scale.